Leadership in Action : In Focus--Dealing with Change--Leading Globally Requires a Fundamental Shift - Livers, Ancella (Center for Creative Leadership, 2007)
Although many executives recognize that moving into a global position requires them to manage under multiple sets of laws, currencies, and time zones, many don't understand that to lead in a global setting requires a fundamental shift in their thinking and behavior.